2019
DOI: 10.29252/edcj.12.33.103
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Students toward the Quality of Educational Services at Zahedan University of Medical Sciences, Based on the SERVQUAL Model during the Academic Year 2017-2018

Abstract: Background & Objective: Higher education is an important institution providing education and human resources, which requires special attention in terms of the quality of services if it is to be preserved. The present study aimed to assess the perceptions of students toward the quality of educational services at Zahedan University of Medical Sciences (ZAUMS), Iran during the academic year 2017-2018. Materials and Methods: This cross-sectional, descriptive-analytical study was conducted on 477 students, who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Shahroudi Somayeh The study assessed five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shahroudi Somayeh The study assessed five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khandan et al, (2015) evaluated the QES among students of Kerman Nursing and Midwifery School according to the SERVQUAL model and demonstrated that it has seen a negative gap in all domains of the QES and also the greatest gap was seen in the domains of tangibility and responsiveness and the lowest gap was found in the assurance dimension. Shahroudi et al, (2019) conducted a study on 477 students of Zahedan University of Medical Sciences to investigate the quality of QES" the SERVQUAL model and according to their results, only 1% of the participants described the quality of educational services as favorable. Daryazadeh et al, (2022) employed the SERVQUAL model to evaluate the QES from the perspective of medical students and clinical teachers of Kashan University of Medical Sciences.…”
Section: Introductionmentioning
confidence: 99%